2022
DOI: 10.3390/jmse10050620
|View full text |Cite
|
Sign up to set email alerts
|

Early Succession Patterns of Benthic Assemblages on Artificial Reefs in the Oligotrophic Eastern Mediterranean Basin

Abstract: The colonization of artificial structures by benthic organisms in the marine realm is known to be affected by the general trophic patterns of the biogeographical zone and the prevailing environmental traits at the local scale. The present work aims to present quantitative data on the early settlement progress of macrofaunal benthic assemblages developing on artificial reefs (ARs) deployed at the Underwater Biotechnological Park of Crete (UBPC) in the oligotrophic Eastern Mediterranean. Visual census and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…While statistically significant, others have reported increases in erect sponges in a depth-dependent way, suggesting a selection in growth and colonization due to tidal wave action [66]. The lack of erect sponges is supported by reports of other young (>3 years) concrete artificial reefs, where only encrusting sponges were detected [67]. Sponges previously were considered a 'fouling' species, which many times prepare the area for coral colonization [68], but some recent data suggest they may reduce coral recruitment through space competition [69,70].…”
Section: Discussionmentioning
confidence: 79%
“…While statistically significant, others have reported increases in erect sponges in a depth-dependent way, suggesting a selection in growth and colonization due to tidal wave action [66]. The lack of erect sponges is supported by reports of other young (>3 years) concrete artificial reefs, where only encrusting sponges were detected [67]. Sponges previously were considered a 'fouling' species, which many times prepare the area for coral colonization [68], but some recent data suggest they may reduce coral recruitment through space competition [69,70].…”
Section: Discussionmentioning
confidence: 79%
“…Early studies on the colonization of artificial structures in the NW Mediterranean indicated that it takes approximately 3 years for the community to reach a mature stage in terms of both biomass [72] and species composition [73,74]. Similar experiences in other seas, however, have shown that climax communities were reached in 5 to 20 years [75][76][77], but the differences between natural and artificial reefs have been observed to persist even for much longer times [71,78,79]. At St. Eustatius (eastern Caribbean), no significant difference in the density of coral-associated fauna was found between a centuries-old manmade structure and the nearest natural reef [49], notwithstanding differences in relief rugosity and surface structure, which are also known to exert an important influence on the entire epibenthic community [52,80].…”
Section: Discussionmentioning
confidence: 98%
“…However, approximately two years after deployment most species have settled into the habitat and, thereafter, begin to establish themselves, reaching climax communities in 5 to 20 years (Hawkins et al, 1983;Pinn et al, 2005;Gacia et al, 2007;Coombes, 2011). Nevertheless, and despite these being dynamic communities, the differences between natural and artificial coastlines can persist even in centuries-old artificial structures, regardless of the substrate they are made of, indicating that, in general, artificial shorelines are poor surrogates of natural habitats (Firth et al, 2016;Hill et al, 2021;Rallis et al, 2022). Artificial structures such as seawalls have low structural complexity at various spatial scales and a low presence of tide pools, pits, grooves, bumps, ledges, and crevices, which reduce microhabitats' heterogeneity when compared to natural areas (Moreira et al, 2006;Loke and Todd, 2016;Cacabelos et al, 2018;MacArthur et al, 2020;Strain et al, 2020).…”
Section: Introductionmentioning
confidence: 99%